Persistent dyspnea after COVID-19 is not related to cardiopulmonary impairment; a cross-sectional study of persistently dyspneic COVID-19, non-dyspneic COVID-19 and controls - Beaudry, Rhys I.; Brotto, Andrew R.; Varughese, Rhea A.; de Waal, Stephanie; Fuhr, Desi P.; Damant, Ronald W.; Ferrara, Giovanni; Lam, Grace Y.; Smith, Maeve P.; Stickland, Michael K. (Frontiers in Physiology, 2022)
Background: Up to 53% of individuals who had mild COVID-19 experience symptoms for >3-months following infection (Long-CoV). Dyspnea is reported in 60% of Long-CoV cases and may be secondary to impaired exercise capacity (VO2peak) as a result of pulmonary, pulmonary vascular, or cardiac insult. This study examined whether cardiopulmonary mechanisms could explain exertional dyspnea in Long-CoV. Methods: A cross-sectional study of participants with Long-CoV (n=28, age 40±11 years, 214±85 days post-infection) and age- sex- and body mass index-matched COVID-19 naïve controls (Con, n=24, age 41±12 years) and participants fully recovered from COVID-19 (ns-CoV, n=14, age 37±9 years, 198±89 days post-infection) was conducted. Participants self-reported symptoms and baseline dyspnea (modified Medical Research Council, mMRC, dyspnea grade), then underwent a comprehensive pulmonary function test, cardiopulmonary exercise test, exercise pulmonary diffusing capacity measurement, and rest and exercise echocardiography. Results: VO2peak, pulmonary function and cardiac/pulmonary vascular parameters were not impaired in Long- or ns-CoV compared to normative values (VO2peak: 106±25 and 107±25%predicted, respectively) and cardiopulmonary responses to exercise were otherwise normal. When Long-CoV were stratified by clinical dyspnea severity (mMRC=0 vs. mMRC≥1), there were no between-group differences in VO2peak. During submaximal exercise, dyspnea and ventilation were increased in the mMRC≥1 group, despite normal operating lung volumes, arterial saturation, diffusing capacity and indicators of pulmonary vascular pressures. Interpretation: Persistent dyspnea after COVID-19 was not associated with overt cardiopulmonary impairment or exercise intolerance. Interventions focusing on dyspnea management may be appropriate for Long-CoV patients who report dyspnea without cardiopulmonary impairment.